Mirror self-face perception in individuals with schizophrenia: Feelings of strangeness associated with one's own image. (July 2017) - Bortolon, Catherine; Capdevielle, Delphine; Altman, Rosalie; Macgregor, Alexandra; Attal, Jérôme; Raffard, Stéphane
Abstract: Self-face recognition is crucial for sense of identity and for maintaining a coherent sense of self. Most of our daily life experiences with the image of our own face happen when we look at ourselves in the mirror. However, to date, mirror self-perception in schizophrenia has received little attention despite evidence that face recognition deficits and self abnormalities have been described in schizophrenia. Thus, this study aims to investigate mirror self-face perception in schizophrenia patients and its correlation with clinical symptoms. Twenty-four schizophrenia patients and twenty-five healthy controls were explicitly requested to describe their image in detail during 2 min whilst looking at themselves in a mirror. Then, they were asked to report whether they experienced any self-face recognition difficulties. Results showed that schizophrenia patients reported more feelings of strangeness towards their face compared to healthy controls (U=209.5, p =0.048, r=0.28), but no statistically significant differences were found regarding misidentification ( p =0.111) and failures in recognition ( p =0.081). Symptoms such as hallucinations, somatic concerns and depression were also associated with self-face perception abnormalities (all p- values>0.05). Feelings of strangeness toward one's own face in schizophrenia might be part of a familiar face perception deficit or a more global self-disturbance, which is characterized by a loss of self-other boundaries and has been associated with abnormal body experiences and first rank symptoms. Regarding this last hypothesis, multisensorial integration might have an impact on the way patients perceive themselves since it has an important role in mirror self-perception. Highlights: SZ reported more feelings of self-face strangeness. Self-face strangeness was associated with hallucinations. Self-face strangeness was associated with somatic concerns.